IMMERSIVE INSTRUCTIONAL DESIGN DEVELOPMENT USING EXTENDED REALITY (XR) TO ENHANCE LEARNING ENGAGEMENT - Indrakusuma, Abdul Haris (STKIP PGRI Tulungagung, 2024)
This study develops an immersive instructional design framework using Extended Reality (XR) technologies Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR) to enhance learner engagement in digital learning environments. Addressing the limitations of traditional instructional methods in online settings, the study adopts a Design-Based Research (DBR) approach through three phases: analyzing learner needs, developing XR-based modules, and evaluating engagement and outcomes. Data from surveys, observations, and interviews with undergraduates indicate significant improvements in cognitive involvement, emotional connection, and motivation. The iterative process enabled ongoing refinement, contributing a practical model for XR integration in education. The findings offer insights for educators and policymakers to advance digital pedagogy through immersive technologies and extend the theoretical understanding of engagement in digital learning.